Punctuation Practice and Rhetorical Moves in Early English Medical Recipes - Calle-Martín, Javier; Romero-Barranco, Jesús (My University, 2022)
Early English medical recipes constitute a text type characterized by a fixed text structure with a series of rhetorical moves: title, ingredients, application, efficacy and practitioner’s personal experience (Romero-Barranco 2017). Being a text type to which members of all social classes had access, the study of early English medical recipes could shed some new light on the pragmatics on punctuation and, more specifically, on the way in which punctuation marks the transition from one rhetorical move to the next. As stated by Smith, “shifts in punctuation practices correlate with changing patterns of literacy [and] socio-cultural developments […] correlate quite closely with changes in the formal appearance of texts, including punctuation” (2020: 208; see also Smith 2013). In this chapter we analyse the pragmatic dimension of punctuation in early English medical recipe books (1400-1700). For the purpose, medical recipes belonging to 15th, 16th and 17th centuries will be retrieved from The Málaga Corpus of Early English Scientific Prose (http://hunter.uma.es – http://modernmss.uma.es) and, subsequently, their punctuation systems will be analysed. The study pursues the following objectives: 1) to compare the punctuation systems in the recipes both synchronically and diachronically; 2) to elaborate a typology of punctuation symbols that mark the beginning of a new rhetorical move in each period under study; and 3) to ascertain whether rhetorical moves are signalled using the same punctuation symbol over time.
Keywords: Medicina - Fórmulas y recetas; Puntuación; Pragmática; Inglés medio; Inglés moderno temprano